Factorise (y2- y - 12) and divide it by (y - 4)

Dear Student,

y2-y-12y-4=y2-4y+3y-12y-4                    =yy-4+3y-4y-4                    =y-4y+3y-4                    =y+3y2-y-12y-4=y+3

Hope this information will clear your doubts about the topic.                                                                                            

If you have any more doubts, just ask here on the forum and our expert will try to help you out as soon as possible.                                                                                                      


  • 0
What are you looking for?